Dramatic Response of an Aggressive Chest Wall Recurrence to Hyperthermia, Radiation, and Chemotherapy - Cohen, Justin (Cureus, 2017)
Hyperthermia has been demonstrated to be an effective adjuvant oncological treatment modality in combination with chemotherapy and/or radiation. Published data have demonstrated that the addition of hyperthermia can improve local control for breast cancer chest wall recurrences. We present a patient with a very aggressive estrogen receptor-negative, progesterone receptor-negative, HER2/neu receptor-negative chest wall recurrence status-post a right modified radical mastectomy. Despite having metastatic disease, in an attempt to achieve local control and provide palliation, she was treated with hyperthermia, radiation, and chemotherapy. A near complete resolution of her chest wall recurrence in a very short time period was seen with a significant improvement in her symptoms. While she unfortunately succumbed to her disease shortly thereafter, the local control that our treatment offered her allowed her quality of life to improve significantly near the end of her life.